Heat transfer due to revolving flow of Reiner-Rivlin fluid over a stretchable surface. (May 2019) - Sahoo, Bikash; Shevchuk, Igor V.
Highlights: Non-Newtonian Reiner-Rivlin fluid. Swirling flow. Stretchable surface. Oscillatory velocity profiles. Heat transfer. Abstract: The interaction of rotating flow and a stationary stretchable surface is discussed for a non-Newtonian Reiner-Rivlin fluid. The radial variation of the disk's surface temperature follows a power law. Similarity solutions of the governing partial differential equations are obtained for the case of the outer flow in solid-body rotation. The resulting coupled and highly nonlinear system of equations are solved numerically. The solutions indicate that the disk stretching has prominent effects on both momentum and thermal boundary layers. The strength of the induced secondary flow in the boundary layer decreases significantly with an increase in the stretching parameter. Stretching dominates the oscillatory nature of the velocity profiles. As a result of reduction in the momentum boundary layer, the thermal boundary layer thickness decreases significantly with an increase in the radial stretching. On the other hand, shrinking of the disk has opposite effects on the boundary layers. An asymptotic analysis has also been carried out to support the obtained numerical results.